Fuel consumption in empirical synchronised flow in urban traffic. Issue 2 (1st March 2016) - Hemmerle, Peter; Koller, Micha; Rehborn, Hubert; Kerner, Boris S.; Schreckenberg, Michael
Abstract : Based on an empirical study of real field global positioning system data obtained from navigation devices in vehicles, the authors analyse fuel consumption of vehicles in city traffic. They show that synchronised flow patterns, revealed recently in real field oversaturated city traffic, exhibit considerable impact on fuel consumption. In particular, they have found out that fuel consumption in oversaturated city traffic can decrease considerably when oversaturated city traffic consists of synchronised flow patterns rather than consisting of moving queues of the classical traffic flow theory at traffic signals. Using empirical data from two different road sections in the city of Düsseldorf, Germany, the authors show that synchronised flow patterns and moving queues differ in their cumulated vehicle acceleration (a sum of positive speed differences along a vehicle trajectory) despite similar mean vehicle speeds. Fuel consumption in return is dependent on the cumulated vehicle acceleration. This latter dependency is obtained by means of a macroscopic consumption matrix based on empirical field trial consumption data and simulated speed and acceleration profiles. The authors sketch out the application of the study results to route guidance by demonstrating that the most energy‐efficient route in a road network can differ from the fastest route.